Low-value injury care in the adult orthopaedic trauma population: a protocol for a rapid review. Issue 3 (18th March 2020) - Bérubé, Mélanie; Moore, Lynne; Leduc, Stéphane; Farhat, Imen; Lesieur, Martin; Lamontagne, Jean; Pelet, Stéphane; Berry, Gregory; Tardif, Pier-Alexandre; Côté, Caroline; Paquet, Jérôme
Abstract : Introduction: Orthopaedic injuries affect almost 90% of trauma patients. A previous scoping review and expert consultation survey identified 15 potential low-value intra-hospital practices in the adult orthopaedic trauma population. Limiting the frequency of such practices could reduce adverse events, improve clinical outcomes and free up resources. The aim of this study is to synthesise the evidence on intra-hospital practices for orthopaedic injuries, previously identified as potentially of low value. Methods and analysis: We will search Medline, Excerpta Medica Database (EMBASE), the Cochrane Central Register of Controlled Trials and Epistemonikos to identify systematic reviews, randomised controlled trials (RCTs), quasi-RCTs, cohort studies and case–control studies that evaluate selected practices according to a priori PICOS statements (Population–Intervention–Comparator–Outcome–Study design) . We will evaluate the methodological quality for systematic reviews using the Measurement Tool to Assess Systematic Reviews version 2 (AMSTAR-2). Risk of bias in original studies will be evaluated with the Cochrane revised tool for RCTs (RoB2) and with the risk of bias in non-randomised studies of interventions (ROBINS-I) tool. If for a given practice, more than two original studies on our primary outcome are identified, we will conduct meta-analysis using a random effects model and assess heterogeneity using the I 2 index. We will assess credibility of evidence (I–IV) based on statistical significance, sample size, heterogeneity and bias as per published criteria. Ethics and dissemination: Ethics approval is not required as original data will not be collected. Knowledge users from three level I trauma centres are involved in the design and conduct of the study in accordance with an integrated knowledge translation approach. Findings related to the rapid review will be available in May 2020. They will be presented to key stakeholders to inform discussions and raise awareness on low-value injury care. In addition, results will be disseminated in a peer-reviewed journal, at national and international scientific meetings and to healthcare associations.